Comparison of growth and feeding method in infants with and without genetic abnormalities after neonatal cardiac surgery. (25th December 2020) - Pierick, Alyson R.; Pierick, Trudy A.; Reinking, Benjamin E.
Abstract: Introduction: Congenital heart disease (CHD) is multifactorial in origin, resulting from an interaction between environmental and genetic factors. Multifactorial growth delay is common in infants with CHD. The impact of a genetic abnormality and CHD on the growth of an infant is lacking in the literature. The aim of this study is to compare the growth and method of feeding following neonatal cardiac surgery in infants with normal versus abnormal genetic testing. Methods: A retrospective chart review of neonates who underwent a Risk Adjustment in Congenital Heart Surgery IV–VI procedure between 1 January, 2006 and 22 September, 2016 was performed at our institution. Weight, length, head circumference measurements, and feeding method were collected at birth, time of neonatal surgery, and monthly up to 6 months of age. Results: A total of 53 infants met inclusion criteria, of which 22 had abnormal genetic testing. Approximately 90% of infants were discharged following neonatal cardiac surgery with supplemental tube feeds. At each monthly follow-up visit, more infants were exclusively fed orally: 80% of infants with normal genetics at 5 months post-operative follow-up versus 60% of infants with abnormal genetic testing, although statistically insignificant. Growth was not different among the two groups. Conclusions: Infants with critical CHD with or without genetic abnormalities are at risk for growth delays and many need supplemental tube feeds post-operatively and throughout follow-up. Infants with genetic abnormalities are slower to achieve oral feeds and more likely to require tube feedings. It is important to have a systematic protocol for managing these high-risk infants.